High-liquid-storage heat-resistant composite diaphragm

By adopting a composite structure of functional coating and heat-resistant ceramic coating in the lithium battery separator, the problem of insufficient heat resistance and liquid storage properties of the separator is solved, and the circulation and safety performance of the battery cell are significantly improved.

CN119581796APending Publication Date: 2025-03-07NINGDE ZHUOGAO NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411775099.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing lithium battery separators lack heat resistance and liquid storage properties, which leads to the battery cell being easily short-circuited at high temperatures, and the growth of lithium dendrites affects the cycling performance of the battery cell.

Method used

A functional coating between the first base film and the second base film is employed, the coating including an organic inorganic hybrid coating and an ionic conductor coating, combined with a heat-resistant ceramic coating to form a composite coated separator.

Benefits of technology

It reduces the risk of lithium dendrites piercing the diaphragm, improves the liquid storage performance of the diaphragm, and enhances the overall circulation and safety performance of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581796A_ABST
    Figure CN119581796A_ABST
Patent Text Reader

Abstract

The invention discloses a high liquid storage heat-resistant composite diaphragm, which comprises a first base membrane and a second base membrane, a functional coating is arranged between the first base membrane and the second base membrane, one side of the second base membrane far away from the first base membrane is coated with a heat-resistant ceramic coating, the functional coating comprises a first strip-shaped coating and a second strip-shaped coating which are alternately distributed, and the first strip-shaped coating and the second strip-shaped coating are coated with a heat-resistant ceramic coating. The coating thickness of the first strip-shaped coating is larger than that of the second strip-shaped coating, the first strip-shaped coating is an organic-inorganic mixed coating, the organic-inorganic mixed coating is respectively connected with the first base membrane and the second base membrane in a bonding manner, and the second strip-shaped coating is an ion conductor coating. The risk that the lithium dendrites pierce the diaphragm is reduced, meanwhile, further growth of the lithium dendrites can be effectively relieved, and the capacity loss of the battery is avoided; and the first strip-shaped coating and the second strip-shaped coating in the functional coating have high and low thicknesses, so that more spaces are created for storing electrolyte, and the battery capacity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery separators, and in particular to a high liquid storage and heat-resistant composite separator. Background Art

[0002] As an important component of lithium batteries, the performance of the diaphragm has a decisive influence on the performance of the battery cell. The diaphragm itself has poor heat resistance, and a heat-resistant ceramic layer needs to be coated on its surface to improve the heat resistance of the diaphragm, reduce the risk of short circuit of the positive and negative electrodes of the battery cell due to the shrinkage of the diaphragm at high temperatures, and increase the safety performance of the battery cell; the liquid storage capacity of the diaphragm can affect the overall capacity of the battery. The diaphragm with good liquid storage performance can increase the capacity of the battery cell and improve the cycle performance. In addition, the diaphragm with good liquid storage performance can significantly improve the lithium dendrite phenomenon of the battery cell. The generation of lithium dendrites will seriously affect the overall cycle performance of the battery cell, resulting in a large attenuation of the battery cell capacity. Therefore, it is necessary to develop a multifunctional diaphragm that can maintain the heat resistance of the diaphragm while storing more electrolyte, and at the same time alleviate the further growth of lithium dendrites, thereby improving the overall cycle performance and safety performance of the battery cell. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a high liquid storage and heat-resistant composite diaphragm, which can reduce the risk of lithium dendrites piercing the diaphragm and improve the liquid storage performance of the diaphragm while maintaining the heat resistance of the diaphragm, thereby improving the overall cycle performance and safety performance of the battery cell.

[0004] To achieve the above purpose, the present invention adopts the following technical solutions:

[0005] A high liquid storage heat-resistant composite diaphragm includes a first base film and a second base film, a functional coating is provided between the first base film and the second base film, a heat-resistant ceramic coating is coated on the side of the second base film away from the first base film, the functional coating includes a first strip coating and a second strip coating distributed alternately, the coating thickness of the first strip coating is greater than the coating thickness of the second strip coating, the first strip coating is an organic-inorganic mixed coating, the organic-inorganic mixed coating is bonded to the first base film and the second base film respectively, and the second strip coating is an ion conductor coating. The composite coated diaphragm is obtained by compounding the first base film, the second base film and the functional coating, which reduces the risk of lithium dendrites piercing the diaphragm, and at the same time, the second strip coating in the functional coating can provide sufficient lithium supplementation effect, which can effectively alleviate the further growth of lithium dendrites and avoid battery capacity loss; and the first strip coating and the second strip coating in the functional coating have different thicknesses, so as to create more space to store electrolyte, thereby increasing battery capacity.

[0006] As a preferred technical solution, the first strip coating and the second strip coating have the same extension direction, and the angle between the extension direction of the first strip coating and the second strip coating and the TD direction of the diaphragm is 0 to 45°. Preferably, it is 0 to 35°, and optimally, it is 0 to 25°. By making the extension direction of the first strip coating and the second strip coating form a certain angle with the TD direction of the diaphragm, it is beneficial to the injection of the electrolyte after the battery is wound, improve the injection efficiency, and reduce the manufacturing cost.

[0007] As a preferred technical solution, the distance between the second stripe coating and the adjacent first stripe coating is 0-100 μm.

[0008] As a preferred technical solution, the first base film is a PP film, the thickness of the PP film is 7 to 16 μm, and the second base film is a PE film, the thickness of the PE film is 5 to 12 μm.

[0009] As a preferred technical solution, the width of the first strip coating is 300-500 μm, and the coating thickness is 3-5 μm; the width of the second strip coating is 500-800 μm, and the coating thickness is 1-3 μm; the difference in coating thickness between the first strip coating and the second strip coating is 1.5-4 μm.

[0010] As a preferred technical solution, one side of the second strip coating is bonded to the PE film, and a gap is retained between the other side and the PP film.

[0011] As a preferred technical solution, the organic-inorganic hybrid coating includes an organic binder, inorganic ceramic particles, a diaphragm binder and a wetting agent; wherein the inorganic ceramic particles account for a proportion of greater than 70% and less than 90% of the total mass of the organic-inorganic hybrid coating; and the organic binder accounts for a proportion of greater than 10% and less than 30% of the total mass of the organic-inorganic hybrid coating.

[0012] As a preferred technical solution, the inorganic ceramic particles include one or more of alumina, boehmite, zirconium oxide, zinc oxide, silicon dioxide, and magnesium hydroxide, and the particle size D50 of the inorganic ceramic particles is 0.3 to 1.0 μm; the organic binder includes one or two of PMMA and PVDF, and the particle size D50 of the organic binder is 4 to 8 μm.

[0013] As a preferred technical solution, the ion conductor coating comprises an ion conductor material, a membrane binder and a wetting agent, wherein the ion conductor material accounts for more than 90% of the total mass of the ion conductor coating.

[0014] As a preferred technical solution, the heat-resistant ceramic layer includes heat-resistant ceramic particles, a diaphragm binder and a wetting agent, and the particle size D50 of the heat-resistant ceramic particles is 0.5 to 1.0 μm. By coating the heat-resistant ceramic layer on the non-composite surface of the second base film, the heat resistance of the entire diaphragm can be improved, so that the thermal shrinkage rate of the composite diaphragm in the MD and TD directions is less than 5% under the condition of baking at 150°C for 1 hour.

[0015] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, a composite coated diaphragm is obtained by compounding a first base film, a second base film and a functional coating, which reduces the risk of lithium dendrites piercing the diaphragm. At the same time, the second strip coating in the functional coating can provide sufficient lithium replenishment effect, which can effectively alleviate the further growth of lithium dendrites and avoid battery capacity loss; and the first strip coating and the second strip coating in the functional coating have different thicknesses, so as to create more space to store electrolyte, thereby improving the battery capacity.

[0016] In order to more clearly explain the structural features, technical means and specific purposes and functions achieved by the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments: BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic cross-sectional structure diagram of the first embodiment of the present invention;

[0018] Figure 2 is a schematic diagram of a top view of the functional coating of Example 1 of the present invention;

[0019] Figure 3 is a schematic cross-sectional structure diagram of the second embodiment of the present invention;

[0020] Figure 4 It is a schematic diagram of the top view of the functional coating of Example 2 of the present invention.

[0021] Description of the accompanying drawings:

[0022] 10. First base film 20, second base film 30, functional coating

[0023] 31. First stripe coating 32. Second stripe coating 40. Heat-resistant ceramic coating. DETAILED DESCRIPTION

[0024] In the description of the present invention, it should be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" etc. indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the positions or elements referred to must have specific directions, be constructed and operated in specific directions. Therefore, they should not be understood as limitations on the present invention.

[0025] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0026] like Figure 1-4 As shown, a high liquid storage and heat-resistant composite diaphragm of the present invention includes a first base film 10 and a second base film 20, a functional coating 30 is provided between the first base film 10 and the second base film 20, and a heat-resistant ceramic coating 40 is coated on the side of the second base film 20 away from the first base film 10, the functional coating 30 includes a first strip coating 31 and a second strip coating 32 distributed alternately, the coating thickness of the first strip coating 31 is greater than the coating thickness of the second strip coating 32, the first strip coating 31 is an organic-inorganic hybrid coating, the organic-inorganic hybrid coating is respectively bonded to the first base film 10 and the second base film 20, and the second strip coating 32 is an ion conductor coating. A composite coated diaphragm is obtained by compounding the first base film 10, the second base film 20 and the functional coating 30, which reduces the risk of lithium dendrites piercing the diaphragm. At the same time, the second strip coating 32 in the functional coating 30 can provide sufficient lithium replenishment effect, which can effectively alleviate the further growth of lithium dendrites and avoid battery capacity loss; and the first strip coating 31 and the second strip coating 32 in the functional coating 30 have different thicknesses, so as to create more space to store electrolyte, thereby increasing the battery capacity.

[0027] In the present invention, the first base film 10 is a PP film, the thickness of the PP film is 7-16 μm, and the second base film 20 is a PE film, the thickness of the PE film is 5-12 μm. The width of the first strip coating 31 is 300-500 μm, and the coating thickness is 3-5 μm; the width of the second strip coating 32 is 500-800 μm, and the coating thickness is 1-3 μm; the coating thickness difference between the first strip coating 31 and the second strip coating 32 is 1.5-4 μm, and one side of the second strip coating 32 is bonded to the PE film, and a gap is reserved between the other side and the PP film. The thickness of the heat-resistant ceramic coating 40 is 1.5-4.0 μm.

[0028] Specifically, the first strip coating 31 and the second strip coating 32 have the same extension direction, and the angle between the extension direction of the first strip coating 31 and the second strip coating 32 and the TD direction of the separator is 0 to 45°, preferably 0 to 35°, and optimally 0 to 25°. By making the extension direction of the first strip coating 31 and the second strip coating 32 form a certain angle with the TD direction of the separator, it is beneficial to inject the electrolyte after the battery is wound, improve the injection efficiency, and reduce the manufacturing cost.

[0029] Specifically, the organic-inorganic hybrid coating includes an organic binder, inorganic ceramic particles, a diaphragm binder and a wetting agent; wherein the inorganic ceramic particles account for a proportion of greater than 70% and less than 90% of the total mass of the organic-inorganic hybrid coating; the organic binder accounts for a proportion of greater than 10% and less than 30% of the total mass of the organic-inorganic hybrid coating; the particle size D50 of the inorganic ceramic particles is 0.3 to 1.0 μm; the organic binder includes one or both of PMMA and PVDF, and the particle size D50 of the organic binder is 4 to 8 μm.

[0030] The heat-resistant ceramic layer includes heat-resistant ceramic particles, a diaphragm binder and a wetting agent. The particle size D50 of the heat-resistant ceramic particles is 0.5 to 1.0 μm. By coating the heat-resistant ceramic layer on the non-composite surface of the second base film 20, the heat resistance of the entire diaphragm can be improved, so that the thermal shrinkage rate of the composite diaphragm in the MD and TD directions is less than 5% under the condition of baking at 150°C for 1 hour.

[0031] The ion conductor coating comprises an ion conductor material, a membrane binder and a wetting agent, wherein the ion conductor material accounts for more than 90% of the total mass of the ion conductor coating. The ion conductor material comprises one or two of LATP, LLZTO, LLZO and Li3InCl6.

[0032] The inorganic ceramic particles in the organic-inorganic hybrid coating and the heat-resistant ceramic particles in the heat-resistant ceramic layer include one or more of aluminum oxide, boehmite, zirconium oxide, zinc oxide, silicon dioxide, and magnesium hydroxide, and the diaphragm binder is selected from one of polyacrylic acid, polymethyl acrylate, polyethyl acrylate, or SBR;

[0033] In the present invention, the distance between the second stripe coating 32 and the adjacent first stripe coating 31 is 0 to 100 μm, preferably 0 to 70 μm, and more preferably 0 to 40 μm. Figure 1 and Figure 2 As shown in the first embodiment of the present invention, the second strip coating 32 is seamlessly connected to the adjacent first strip coating 31; Figure 3 and Figure 4 As shown, in the second embodiment of the present invention, a gap is reserved between the second strip coating 32 and the adjacent first strip coating 31 , that is, the first strip coating 31 and the second strip coating 32 are not fully coated on the surface of the second base film 20 .

[0034] In summary, the present invention obtains a composite coated diaphragm by compositely combining a first base film, a second base film and a functional coating, which reduces the risk of lithium dendrites piercing the diaphragm. At the same time, the second strip coating in the functional coating can provide sufficient lithium replenishment effect, which can effectively alleviate the further growth of lithium dendrites and avoid battery capacity loss; and the first strip coating and the second strip coating in the functional coating have different thicknesses, thereby creating more space to store electrolyte, thereby increasing the battery capacity.

[0035] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Therefore, any modification, equivalent replacement, improvement, etc. made to the above embodiment based on the technical practice of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A high liquid storage heat-resistant composite diaphragm, characterized in that: It includes a first base film and a second base film, a functional coating is arranged between the first base film and the second base film, a side of the second base film away from the first base film is coated with a heat-resistant ceramic coating, the functional coating includes a first strip coating and a second strip coating distributed alternately, the coating thickness of the first strip coating is greater than the coating thickness of the second strip coating, the first strip coating is an organic-inorganic hybrid coating, the two sides of the organic-inorganic hybrid coating are respectively bonded to the first base film and the second base film, and the second strip coating is an ion conductor coating.

2. A high liquid storage heat-resistant composite diaphragm according to claim 1, characterized in that: The first stripe coating and the second stripe coating have the same extension direction, and the angle between the extension direction of the first stripe coating and the second stripe coating and the TD direction of the separator is 0-45°.

3. A high liquid storage heat-resistant composite diaphragm according to claim 2, characterized in that: The distance between the second stripe coating and the adjacent first stripe coating is 0-100 μm.

4. The high liquid storage heat-resistant composite diaphragm according to claim 1, characterized in that: The first base film is a PP film, and the thickness of the PP film is 7 to 16 μm. The second base film is a PE film, and the thickness of the PE film is 5 to 12 μm.

5. The high liquid storage heat-resistant composite diaphragm according to claim 4, characterized in that: The width of the first stripe coating is 300-500 μm, and the coating thickness is 3-5 μm; the width of the second stripe coating is 500-800 μm, and the coating thickness is 1-3 μm; and the coating thickness difference between the first stripe coating and the second stripe coating is 1.5-4 μm.

6. The high liquid storage heat-resistant composite diaphragm according to claim 5, characterized in that: One side of the second strip coating is bonded to the PE film, and a gap is reserved between the other side and the PP film.

7. The high liquid storage heat-resistant composite diaphragm according to claim 1, characterized in that: The organic-inorganic hybrid coating includes an organic binder, inorganic ceramic particles, a diaphragm binder and a wetting agent; wherein the inorganic ceramic particles account for a proportion of greater than 70% and less than 90% of the total mass of the organic-inorganic hybrid coating; and the organic binder accounts for a proportion of greater than 10% and less than 30% of the total mass of the organic-inorganic hybrid coating.

8. The high liquid storage heat-resistant composite diaphragm according to claim 7, characterized in that: The inorganic ceramic particles include one or more of alumina, boehmite, zirconium oxide, zinc oxide, silicon dioxide, and magnesium hydroxide, and the particle size D50 of the inorganic ceramic particles is 0.3 to 1.0 μm; the organic binder includes one or two of PMMA and PVDF, and the particle size D50 of the organic binder is 4 to 8 μm.

9. The high liquid storage heat-resistant composite diaphragm according to claim 1, characterized in that: The ion conductor coating comprises an ion conductor material, a membrane binder and a wetting agent, wherein the ion conductor material accounts for more than 90% of the total mass of the ion conductor coating.

10. The high liquid storage heat-resistant composite diaphragm according to claim 1, characterized in that: The heat-resistant ceramic layer comprises heat-resistant ceramic particles, a diaphragm binder and a wetting agent, and the particle size D50 of the heat-resistant ceramic particles is 0.5-1.0 μm.